2018
DOI: 10.1590/s0102-053620180207
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutraceutical quality of tomato under different organic substrates

Abstract: Yield and nutraceutical quality of Sahel tomato cultivar under shade net was evaluated using different mixtures of organic substrates in Coahuila, northern Mexico. The treatments consisted of mixtures using sand (S), vermicompost (VC), solarized bovine manure (SB), agricultural soil (AS) and mineralized compost (MC). The treatments were: T1 (S:VC, 80:20), T2 (S:SB, 80:20), T3 (S:SB:AS, 80:15:05), T4 (S:VC:AS, 80:15:05), T5 (S:MC, 80:20), and a control treatment T6 (S, 100%) with Steiner solution. Yield results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
0
0
3
Order By: Relevance
“…In general terms, the development of muskmelon crops in mixtures of VC:RS, in different ratios, according to Rajbir et al 43 favoured the production of fruits with better quality parameters. Similar effects were determined by Fortis-Hernández et al 44 for tomato fruits, grown under shade house conditions. These authors concluded that organic fertilizers based on the sand-vermicompost mixture (80:20 by percent) increased the phenols content and antioxidant capacity of the crop.…”
Section: Discussionsupporting
confidence: 85%
“…In general terms, the development of muskmelon crops in mixtures of VC:RS, in different ratios, according to Rajbir et al 43 favoured the production of fruits with better quality parameters. Similar effects were determined by Fortis-Hernández et al 44 for tomato fruits, grown under shade house conditions. These authors concluded that organic fertilizers based on the sand-vermicompost mixture (80:20 by percent) increased the phenols content and antioxidant capacity of the crop.…”
Section: Discussionsupporting
confidence: 85%
“…The effect of solarization was evident in our study: in the literature, some reports were available on the possible effects of soil solarization treatment, alone or combined, to improve crop performance and plant nutritional and nutraceutical quality [43,44]. Fortis-Hernández and coworkers [45] studied the effects of different organic substrates, among which solarized bovine manure, on phytochemical features of Solanum lycopersicum L.; the authors reported that some of these treatments, mainly based on compost, induced a good antioxidant capacity. These data highlighted that several chemical substances, such as phenols, seem to be related to the production of antioxidants, which a plant can produce as defense method, in responding to oxidation stress.…”
Section: Antioxidant Activitysupporting
confidence: 53%
“…4). Fortis-Hernández et al (2018) explican que, para el cultivo de tomate, los fertilizantes orgánicos basados en vermicompostas inducen la concentración de licopeno en frutas, así como mejoras en el contenido de fenoles y antioxidantes.…”
Section: Cuantificación De La Capacidad Antioxidanteunclassified